241 IMPLEMENTATION OF AN INTRACEREBRAL CEREBRAL HAEMORRHAGE CARE BUNDLE. (18th November 2021) - Gabr, A; Cunningham, N; Kennedy, C; Mohamed, A; Okpaje, B; Saleh, A; Leahy, A; El-Kholy, K; Carrol, I; Paulose, S; Daly, N; Harnett, A; et al.
Abstract: Background: Mortality for Intracerebral haemorrhage (ICH) is 31% (Irish National Audit Stroke, 2019). An ICH care bundle focusing on acute anticoagulation reversal, blood pressure lowering, and a neurosurgical care pathway was associated with improved survival. Translating evidence-based medicine into clinical practice is challenging. The aim of this study was to determine feasibility and outcomes of implementation of a care bundle. Methods: An ICH care bundle was developed using an iterative process involving expert stakeholder review of the evidence-based literature. A pre-and-post quasi-experimental research design was employed to evaluate this intervention. Baseline data were collected before implementation (January 2016-June 2018). Implementation took place in a staged manner in a single university teaching hospital with multiple 'Plan Do Study Act cycles' (June 2018 to January 2021). Data on compliance, process measures and outcomes were collected. Results: Systolic blood pressure (first 24-hours) and anticoagulant reversal were significantly better controlled post-implementation (χ 2 (1, N = 91) = 5.34, P  = 0.02), (χ 2 (1, N = 25) = 5.85, P  = 0.016), respectively. DNAR orders were significantly lower in the post-implementation group (χ 2 (1, N = 25) = 5.85, P  = 0.029). However, 'Do Not Actively Resuscitate' status did not significantly differ when accounting for low GCS as a surrogate measure for poor prognosis (χ 2 (1, N = 34) = 0.00, P  = 0.966). Modified Rankin Scale on discharge did not differ significantly pre-and-post-implementation (z = −0.075, P  = 0.94). A greater proportion of patients survived in the post-implementation group; however, this was not statistically significant (χ 2 (1, N = 133) = 0.77, P  = 0.38). Length of stay significantly increased post implementation. Conclusion: An ICH care bundle was developed based on expert stakeholder feedback. The feasibility of implementing this bundle of care was demonstrated in a real-world clinical practice setting. A cluster-randomized trial or a large registry study is the next step to evaluate the overall impact of this care bundle on patient outcomes.